The Effect of Quora-Based Extensive Reading on EFL Students’ Critical Thinking Skills in Higher Education - Satriani, Estika; Idayani, Andi; Etfita, Fauzul; Ahmad, Arimuliani; Alber, Alber; Kadar, Destry Pryant (Universitas Pahlawan Tuanku Tambusai, 2026)
Critical thinking is a key competence in English as a Foreign Language (EFL) learning, particularly in higher education. This study examines the effect of extensive reading on Quora on EFL students’ critical thinking at the English Language Education Department, Universitas Islam Riau. A quasi-experimental design was employed involving 60 second-semester students divided into an experimental group (n = 30) and a control group (n = 30). The experimental group received extensive reading instruction using Quora, while the control group used conventional materials. Data were collected through pre-test and post-test assessments, adapting Facione’s critical thinking framework. The outcome revealed that the experimental group's mean score increased from 62.40 to 78.60, and the control group improved from 61.90 to 69.30. An independent samples t-test revealed a significant difference between groups (t = 4.85, p 0.05). These findings indicate that Quora-based extensive reading effectively enhances EFL students’ critical thinking.